SOIL QUALITY INDEX IN THE UPSTREAM OF BENGAWAN SOLO RIVER BASIN ACCORDING TO THE SOIL FUNCTION IN NUTRIENT CYCLING BASED ON SOYBEAN PRODUCTION IN AGROFORESTRY - Supriyadi, Supriyadi; Hartati, Sri; Machfiroh, Nur (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Over the function of the upstream region watersheds causes the soil susceptible to degradation of soil fertility. Agroforestry systems that have been implemented should be reviewed to determine their effectiveness in improving soil fertility using a soil quality index. The varieties of soybean that cultivated in the study site were Grobogan, Kaba, and Argomulyo. The variables of this study consists of organic-C, pH, cation exchange capacity (CEC), total-N, available-P, available-K, Na, Ca, Mg, base saturation, and electrical conductivity (EC). Soil quality index calculation performed on selected outcome variables principal component analysis (PCA) which is then multiplied by the weights index on each PC. Selected variables from PCA consist of available-P, available-K, base saturation, and pH. Soil quality index values for all types of Agroforestry in the upstream of Bengawan Solo river basin (Wonogiri) is under secondary forest (<4.1) so that it can be concluded that the adoption of Agroforestry in the upstream of Bengawan Solo river basin has not effect on soil quality based on soil functions in the recycling of nutrients. Mean of soybean grain yield in agroforestry system are higher than the mean of national soybean production, but there are an obstacle such as light conditions.